2007
DOI: 10.1002/ajmg.b.30448
|View full text |Cite
|
Sign up to set email alerts
|

Non‐verbal deficits in young children with a genetic metabolic disorder: WPPSI‐III performance in cystinosis

Abstract: Cystinosis is a recessive genetic metabolic disorder in which the amino acid cystine accumulates in various organs of the body. Previous studies have demonstrated visuospatial dysfunction in children and adults with this disorder. It is not known whether this is a result of the genetic alteration or an accumulation of cystine in the brain over time. This study investigated patterns of performance in 20 young children with cystinosis (4-7 years) and 20 matched controls on the Wechsler Preschool and Primary Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
22
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 16 publications
7
22
1
Order By: Relevance
“…Some study show it is a homophilic receptor expressed on T cells, B cells, dendritic cells, monocytes, macrophages,eosinophils, mast cells, granulocytes, and platelets[14]. CD84 expression increases the following activation of T cells, B cellsand dendritic cells[15]. CD84 is also a hemophilic family member that enhances IFN-_ secretion in activated T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some study show it is a homophilic receptor expressed on T cells, B cells, dendritic cells, monocytes, macrophages,eosinophils, mast cells, granulocytes, and platelets[14]. CD84 expression increases the following activation of T cells, B cellsand dendritic cells[15]. CD84 is also a hemophilic family member that enhances IFN-_ secretion in activated T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Children with cystinosis have mean full scale IQs in the low normal range [99][100][101], with impaired tactile recognition of common objects and difficulty processing visual information [102,103]. Even children with normal composite IQs have low visual memory subtest scores, and their academic performance is usually lower than normal.…”
Section: Late Disease Complicationsmentioning
confidence: 99%
“…Nichols et al showed an association between the degree of cortical atrophy and the severity of impairment in visual short-term memory performance [104]. Others reported that children with cystinosis are at greater than normal risk for developing behavioral difficulties and social problems [99,105]. Besides cystinosis, renal failure, long-standing dialysis, and growth retardation themselves can lead to difficulties in psychosocial adjustment requiring psychotherapy.…”
Section: Late Disease Complicationsmentioning
confidence: 99%
“…Neuropsychological studies have shown that individuals with cystinosis have IQ and language within the normal range [13, 14] but specific nonverbal deficits [15, 16]. In particular, deficits are seen in the domains of visual spatial skills, visual–motor integration, visual memory, and processing speed, with a sparing of visual perception [15–19].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, deficits are seen in the domains of visual spatial skills, visual–motor integration, visual memory, and processing speed, with a sparing of visual perception [15–19]. This specific pattern has been observed across the age range from preschool through adulthood [15, 16, 18], suggesting the possibility that the genetic disorder may exert a very early effect on brain development rather than the neurological effects being the result of a progressive decline in cognitive functioning as cystine continues to accumulate in the brain.…”
Section: Introductionmentioning
confidence: 99%